Transportation of Jeffrey Fluid in Circular Cylinder Tube by Dilating Peristaltic Waves - Tiwari, Shailendra Kumar (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, peristaltic transport of Jeffrey fluid in circular cylinder tube has been studied. A mathematical model has developed to study flow by dilating peristaltic waves under assumption of long wavelength and low Reynolds number approximations. The expressions for velocities, pressure gradient and pressure are obtained. The effects of dilation parameter and ratio of relaxation and retardation times are numerically discussed by graphs. It has concluded that pressure increases with the increases of dilation parameter but decreases when ratio of relaxation to retardation time increases.